Association between metabolic status and gut microbiome in obese populations. Issue 8 (6th August 2021) - Zeng, Qiang; Yang, Zhenyu; Wang, Fei; Li, Dongfang; Liu, Yanhong; Wang, Daxi; Zhao, Xiaolan; Li, Yinhu; Wang, Yu; Feng, Xin; Chen, Jiaxing; Li, Yongli; et al.
Abstract : Despite that obesity is associated with many metabolic diseases, a significant proportion (10–30 %) of obese individuals is recognized as 'metabolically healthy obeses' (MHOs). The aim of the current study is to characterize the gut microbiome for MHOs as compared to 'metabolically unhealthy obeses' (MUOs). We compared the gut microbiome of 172 MHO and 138 MUO individuals from Chongqing (China) (inclined to eat red meat and food with a spicy taste), and performed validation with selected biomarkers in 40 MHOs and 33 MUOs from Quanzhou (China) (inclined to eat seafood and food with a light/bland taste). The genera Alistipes, Faecalibacterium and Odoribacter had increased abundance in both Chongqing and Quanzhou MHOs. We also observed different microbial functions in MUOs compared to MHOs, including an increased abundance of genes associated with glycan biosynthesis and metabolism. In addition, the microbial gene markers identified from the Chongqing cohort bear a moderate accuracy [AUC (area under the operating characteristic curve)=0.69] for classifying MHOs distinct from MUOs in the Quanzhou cohort. These findings indicate that gut microbiome is significantly distinct between MHOs and MUOs, implicating the potential of the gut microbiome in stratification and refined management of obesity.